(untitled) (KMC Journal, 2022)
The umbrella term “lesbian, gay, bisexual, and transgender (LGBT)” is widely used to denote sexual and gender minority individuals. But the discrimination still exists in the medical community regarding the sexual identity because the knowledge about those rights is insufficient. Further, the skills and techniques to provide social and psychological support are not scientific in the medical community. The aim of the study was to assess the medical students’ knowledge and attitude towards LGBT population. This cross-sectional study was carried out in 2017 at Kathmandu University with a sample size of 180 undergraduate and medical intern students. Data was collected using a self-administered questionnaire. Data was analyzed using descriptive and inferential statistics (Mann-Whitney test, Kruskal-Wallis test, t-test and ANOVA). Finding shows the mean score of knowledge was 12.32 (±3.7), and attitude was 73.04 (±9.82). The mean coefficient attitude score was 13.44. Being female students and those who were very frank to teacher had a higher knowledge of LGBT. Similarly, internship medical students had a better attitude towards LGBT than other students. This study found higher knowledge and attitude were highly correlated. Being female students had higher knowledge of LGBT and Internship medical students had better attitude towards LGBT population.